Pathfinding algorithms in game development - Rafiq, Abdul; Tuty Asmawaty, Abdul Kadir; Siti Normaziah, Ihsan (IOP Publishing, 2020)
This review paper provides an overview of a pathfinding algorithm for game development which focuses on the algorithms and their contribution to game development. The algorithms were categorised based on their search performance. The aim of this paper is to investigate and provide insights into pathfinding algorithms for game development in the last 10 years. We summarise all pathfinding algorithms and describe their result in terms of performance (time and memory). The result of this paper is metaheuristic techniques have better performance in terms of time and memory compared to heuristic techniques as a pathfinding algorithm.